Evaluation of Some Liver Function Tests in Clinical Cases of Hepatic Insufficiency in Buffaloes - S. Sridhar (Italian Journal of Animal Science, 2010)
The investigation was conducted on 35 clinical cases of hepatic insufficiency in buffaloes. The cases for study were selected on the basis of clinical symptoms and results of liver function tests. All these cases were anorectic and non-febrile. Non-hepatic causes of inappetance were also ruled out before selecting a case for study. Twenty apparently healthy buffaloes from same areas from where the animals were brought were kept as controls for comparison. Liver function tests like Serum aspartate amino transferase (AST/ SGOT), Serum alkaline phosphatase (SAP), enzyme Serum gamma glutamyl transferase (GGT), Serum total proteins and Serum total bilirubin were performed in all the diseased as well as control animals. Results of the study indicated significantly higher activities of serum enzymes AST, SAP and GGT along with significantly higher levels of serum total bilirubin in diseased buffaloes while serum total protein values were found to be significantly lower compared to healthy controls. It was concluded that these liver function tests can be reliable indicators of hepatic insufficiency in buffaloes.